Comparative evaluation of femtosecond laser-assisted cataract surgery and conventional phacoemulsification in white cataract - Titiyal JS (Dove Medical Press, 2016)
Jeewan S Titiyal, Manpreet Kaur, Archita Singh, Tarun Arora, Namrata Sharma Cornea, Cataract & Refractive Surgery Services, Dr Rajendra Prasad Centre for Ophthalmic Sciences, All India Institute of Medical Sciences, New Delhi, India Purpose: To compare femtosecond laser-assisted capsulotomy with conventional manual capsulorhexis in cases of white cataract.Patients and methods: The prospective comparative study enrolled 80 eyes (80 patients) with white cataract that underwent either femtosecond laser-assisted cataract surgery (Group I, n=40) or conventional manual phacoemulsification (Group II, n=40) at a tertiary care ophthalmic institution. The groups were divided based on the patient’s choice and affordability of the procedure. Capsulotomy/capsulorhexis was evaluated in terms of size, circularity index (4Π [area/perimeter2]), intraocular lens coverage, and continuity. Each group was further subdivided based on the release of white milky fluid on initiation of the capsulotomy/capsulorhexis, and the “fluid” cases were compared with the “no-fluid” cases. The primary outcome measure was capsulotomy/capsulorhexis characteristics in the two groups. The secondary outcome measures were intraoperative phacoemulsification parameters, intraoperative complications, and postoperative visual acuity.Results: The size of the capsulotomy/capsulorhexis was 4.9±0.1 mm in Group I and 5.3±0.4 mm in Group II (P<0.001). Mean circularity index was 0.996±0.003 and 0.909±0.047 in Groups I and II, respectively (P<0.001). In Group I, free-floating circular capsulotomies were obtained in 52.5% (21/40) eyes; 37.5% (15/40) eyes had microadhesions; and 10% (4/40) eyes had incomplete capsulotomy in 1–2 clock hours. The incidence of residual adhesions was more in cases with release of white milky fluid (P=0.003). In Group II, a multistep capsulorhexis was performed in 70% (28/40) of the eyes. There was no difference in terms of visual outcomes and intraoperative complications.Conclusion: Femtosecond laser-assisted cataract surgery has the advantage of creating a circular and optimally sized capsulotomy in cases of white cataract. The release of white milky fluid during femtosecond laser delivery is the most important factor affecting the creation of a free-floating capsulotomy. Keywords: femtosecond laser-assisted cataract surgery, white cataract, conventional phacoemulsification, capsulorhexis